Neonatal Morbidities of Fetal Growth Restriction: Pathophysiology and Impact - Malhotra, Atul; Allison, Beth J.; Castillo-Melendez, Margie; Jenkin, Graham; Polglase, Graeme R.; Miller, Suzanne L. (Frontiers in Endocrinology, 2019)
Being born small lays the foundation for short-term and long-term implications for life. Intrauterine or fetal growth restriction describes the pregnancy complication of pathological reduced fetal growth, leading to significant perinatal mortality and morbidity, and subsequent long-term deficits. Placental insufficiency is the principal cause of FGR, which in turn underlies a chronic undersupply of oxygen and nutrients to the fetus. The neonatal morbidities associated with FGR depend on the timing of onset of placental dysfunction and growth restriction, its severity, and the gestation at birth of the infant. In this review, we explore the pathophysiological mechanisms involved in the development of major neonatal morbidities in FGR, and their impact on the health of the infant. Clinical presentation, diagnostic tools and management strategies are presented. We also present information on the current status of targeted therapies. A better understanding of neonatal morbidities associated with FGR will enable early neonatal detection, monitoring and management of potential adverse outcomes in the newborn period and beyond.